GROUP CLAIM AS MEANS TO SPEED UP CIVIL PROCESS - Nekrošius, Vytautas; Simaitis, Rimantas; Vėbraitė, Vigita; Brazdeikis, Aurimas (Teisė, 2016)
In this article, the authors study potential of novelty of Lithuanian civil procedure as of 2015 – the group claim institute – to speed up Lithuanian civil process and some problems related to implementation of such potential. After evaluation of aims to implement group claim institute in Lithuanian civil procedure, the authors recognize that it is justifiable to indicate as a separate aim ensuring of more speedy resolution of mass claims. Nevertheless, practice of submission of group claims to Lithuanian courts is developing slowly. Therefore, currently it is not possible to perform empirical study to what extent the aim to speed up Lithuanian civil process by analysed type of claims is realised in reality. After analysis of different models of groups claims, the authors recognize that opt-out system may ensure better concentration and expedition of process, if compared to opt-in system, which is being implemented in Lithuania and in many other European states. As results of the survey several suggestions for improvement of Code of Civil Procedure of Lithuania are introduced, namely, to foresee mandatory aggregation of all group claims and individual claims of the same type and to define more concise and more reasonable correlation between group claims and individual claims examined under general rules of optional joinder of parties.